Силовые передачи транспортных машин. Динамика и расчет - Алексеева С. В. Серафима Васильевна; Вейц В. Л. Владимир Львович; Геккер Ф. Р. Федор Романович; Кочура А. Е. Александр Евгеньевич (Ленинград, Машиностроение, 1982)
Авт. указаны на обороте тит. л.